IMPLEMENTING QUIZZIZ AS GAME BASED LEARNING IN TEACHING GRAMMAR IN WRITTEN DISCOURSE - Afief Fakhruddin; Eka Nurhidayat; Agus Rofi'i (Universitas PGRI Semarang, 2022)
Quizizz is an online assessment tool as a fun multiplayer classroom activity that allows all students to practice together with their computer, Smartphone and I Pad. The main purpose of this research was to find the effect of implemening quizziz in the discourse classroom of Universitas Majalengka. The population of this research were semester four studens of English department, and the samples were 22 students. This research belongs to pre-experimental research and one group pre and pos test design. It described about a study that cast about the effect of giving treatment of using quizziz in single group only.A pre-experimental research was conducted by comparing the means of the participants’ scores in both pre-test and post-test. The analysis figured out that there was a significant improvement, proven by the paired t-test analysis.The p-value 0.00 was less than alpha 0.05. This research concluded that quizziz was effective to assist the students to learn grammar in written discouse.After implementing quizziz, most of studentsfound that were very active to answer the questions which provided by researches, and more concentrated on the topic. And the results of the questioners shows that the students displayed the position attitude for quizizz as a online teaching and assessment tool during the Grammar in Written Discourse class.